2006
DOI: 10.1007/s00240-005-0019-z
|View full text |Cite
|
Sign up to set email alerts
|

Lithiasis in cystic kidney disease and malformations of the urinary tract

Abstract: The prevalence of renal stones in renal cystic and malformative conditions exceeds the prevalence of renal stones in the general population, suggesting that the above-mentioned cystic and malformative disorders favor stone formation. Urinary stasis is generally assumed to play a major part in the pathogenesis of the nephrolithiasis associated with distorted renal anatomy due to a delayed washout of crystals and risk of urinary infections. However metabolic factors are also important in the pathogenesis of ston… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
41
0
5

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(48 citation statements)
references
References 29 publications
2
41
0
5
Order By: Relevance
“…This observation is consistent with results of previous studies which evaluated the same association in other populations [4][5][6][7] and; with the results obtained in a previous study conducted in the Yucatan population, in which hypocitraturia was found in 63.6% of patients with UL [3]. Given that we did not find any association between I550V-hNaDC-1 genotype and hypocitraturia itself, the genetic contribution of this SNP towards hypocitraturia was not demonstrated in this Mexican population; so the possible genetic basis should be in relation to different implicated genes or different SNPs.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This observation is consistent with results of previous studies which evaluated the same association in other populations [4][5][6][7] and; with the results obtained in a previous study conducted in the Yucatan population, in which hypocitraturia was found in 63.6% of patients with UL [3]. Given that we did not find any association between I550V-hNaDC-1 genotype and hypocitraturia itself, the genetic contribution of this SNP towards hypocitraturia was not demonstrated in this Mexican population; so the possible genetic basis should be in relation to different implicated genes or different SNPs.…”
Section: Discussionsupporting
confidence: 93%
“…Hypocitraturia, which is considered as a urine citrate excretion below 320 mg in 24 hours [2], represents the most common metabolic abnormality in adults with UL [3]. Hypocitraturia is known to be a major risk factor for the development of lithiasis [4][5][6][7], because of citrate acts as a calcium chelating agent, which reduces the formation of oxalate and calcium phosphate, thus inhibiting the generation of urinary calculus [8].…”
Section: Introductionmentioning
confidence: 99%
“…5,6 Major anatomical the metabolic disorders, reducing the recurrence of urinary stones, even in individuals with anatomical alterations. 13 The limitations of the present study comprise its retrospective character and performing only two imaging exams in the patients. However, most anatomical alterations reported in the literature may be assessed by use of both methods.…”
Section: Discussionmentioning
confidence: 95%
“…Cystic dilation of medullary collecting tubules causes urinary stasis which contributes to nephrolithiasis (8). MSK is found in 20% of patients with kidney stones and more than 70% of patients with MSK develop stones (7,9). Nephrolithiasis in MSK facilitates urinary tract infection (3).Dilatation of collecting tubules in MSK also plays role in recurrent pyelonephritis (10).…”
Section: Discussionmentioning
confidence: 99%